Learning for life, friendships and relationships from the perspective of children and young people with intellectual disabilities: findings from a UK wide qualitative study - Michael Brown; Mark Linden; Lynne Marsh; Maria Truesdale; Fintan Sheerin; Freda McCormick (BMC, 2024)
Abstract Background Relationships and sexuality education (RSE) programmes are widely taught in schools, however for children and young people with intellectual disabilities, these programmes appear to be limited regarding information on relationships, informed choices and decision making. The purpose of this study was to seek the views and understanding of children and young people with intellectual disabilities, and those involved in their care and education, to identify best practice and approaches to the delivery on relationships and sexuality education. Methods This study used a qualitative design with 37 pupils from five special schools from across the United Kingdom (UK) participating. In-depth semi-structured interviews were held online, or in person. All interviews were recorded and transcribed verbatim. Transcripts were anonymised, assigned a pseudonym and subjected to inductive thematic analysis. Findings Four themes emerged from the data: (i) enthusiasm and inquisitiveness to acquire knowledge; (ii) dynamics of positive friendships; (iii) experiences and understanding of supportive relationships and sexuality; and (iv) valuing the exchange of knowledge and information. The findings highlight that children and young people with intellectual disabilities want education, support and information on matters relating to their relationships and sexuality. Conclusions This is the largest study to date providing a voice to children and young people with intellectual disabilities regarding their relationships and sexuality. While special schools provide relationships and sexuality education, there is a requirement for a programme and resources specific to the needs of pupils with intellectual disabilities to be developed and evaluated. Such education should continue beyond school and be embedded in adult services.